Professional Sports Organizations and Business Analytics: Monopoly Power vs Debt Financing - Mike Troilo; Adrien Bouchet (Journal of Applied Sports Management, 2022)
In this essay, we consider the factors that explain the reticence of PSOs to be early adopters of analytics. We examine the relatively privileged position that professional sports franchises at the highest echelon in the U.S. and Canada enjoy and compare it the industry dynamics firms face in competitive environments. We remark upon the expansion of the league via debt financing, and why that promotes increased use of analytics. We also offer several propositions about the growth of analytics, and we conclude with some thoughts about what the future may hold for PSOs and analytics.
Keywords: sport analytics; sport management; analytics; monopoly power; debt financing